Gamifying Accelerometer Use Increases Physical Activity Levels of Sedentary Office Workers. Issue 13 (3rd July 2018) - Gremaud, Allene L.; Carr, Lucas J.; Simmering, Jacob E.; Evans, Nicholas J.; Cremer, James F.; Segre, Alberto M.; Polgreen, Linnea A.; Polgreen, Philip M.
Abstract : Background: Sedentary work is hazardous. Over 80% of all US jobs are predominantly sedentary, placing full‐time office workers at increased risk for cardiovascular and metabolic morbidity and mortality. Thus, there is a critical need for effective workplace physical activity interventions. MapTrek is a mobile health platform that gamifies Fitbit use for the purpose of promoting physical activity. The purpose of this study was to test the efficacy of MapTrek for increasing daily steps and moderate‐intensity steps over 10 weeks in a sample of sedentary office workers. Methods and Results: Participants included 146 full‐time sedentary office workers aged 21 to 65 who reported sitting at least 75% of their workday. Each participant received a Fitbit Zip to wear daily throughout the intervention. Participants were randomized to either a: (1) Fitbit‐only group or 2) Fitbit + MapTrek group. Physical activity outcomes and intervention compliance were measured with the Fitbit activity monitor. The Fitbit + MapTrek group significantly increased daily steps (+2092 steps per day) and active minutes (+11.2 min/day) compared to the Fitbit‐only arm, but, on average, participants' steps declined during the study period. Conclusions: MapTrek is an effective approach for increasing physical activity at a clinically meaningful level in sedentary office workers, but as with accelerometer use alone, the effect decreases over time. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03109535.